Albay Selahattin Gürer'in hayatı eserleri ve riyasetindeki Kıyam Kelime-i Tevhidi nin müzikal açıdan incelenmesi - Üstün, Muhammet Enes (My University, 2019)
Dînî mûsikînin, “tekke mûsikîsi” başlığı altında sınıflandırılan ilahi, durak, mi’râciye gibi formlarının yanı sıra en önemli ve büyük formlarından biri de “kıyâm kelime-i tevhîdi”dir. Bu tezde kıyâm kelime-i tevhîdi formu, diğer kıyâm zikri usûlleriyle karşılaştırmalı olarak incelenmiş, tekke mûsikîsinin önemli kurumlarından olan “zâkirbaşılık” ise, Devlet-i Âliye’nin son yıllarında dünyaya gelmiş ve ismini 19. yüzyılın en önemli zâkirbaşıları arasına yazdırmış Albay Selahaddin Gürer özelinde incelenmiştir. Bu sayede bu alanda araştırma yapanlara tekke mûsikîsinin müzikal ve koreografik icrası konusunda müracaat edebilecekleri bir kaynak ortaya koymak suretiyle Türk din mûsikîsine bilimsel bir katkı sağlamak hedeflenmiştir.Tekkelerde icra edilen zikir usûlleri ku’ûdi ve kıyâmî usûllerle sınırlı olmasa da çalışmamızı sınırlandırmak amacıyla yalnızca bu iki tür âyinin koreografisi ve müzikal kısımları detaylıca incelenmiş, devrânî âyinlerden ise kısaca bahsedilmiştir.Kıyâm kelime-i tevhîdînîn müzikal kısmı için kaynak olarak 1960’lı yıllarda yapılan makara kayıtları esas alınmış, bu kayıtlar incelenerek notaya alınmıştır.Bu araştırmada kaynak tarama ve sınıflandırma yöntemlerine başvurulmuştur. Kullanılan verilere Türk Din Mûsikîsi anabilim dalında hazırlanmış tezler, konu uzmanlarıyla yapılan röportajlar, akademik makaleler ve çeşitli kitaplar taranarak ulaşılmış; elde edilen bulgular sınıflandırma yöntemiyle tasnif edilip sistemli bir şekilde işlenmiştir.

“Kıyâm Kelime-i Tevhîdi” (the chanting of the phrase of unity -- “lā ilāha ill'Allah” -- in standing rows facing each other; lit. “The Phrase of Unity in the Standing Position”) is one of the most significant and lengthy forms of Turkish religious music classified under “tekke music”, among other majors forms, such as ilāhi, durak, and mirāciye. In this thesis, “Kıyâm Kelime-i Tevhîdi” has been examined in comparison to the other forms of standing (qiyāmī) remembrance rites. And the position of “zākirbaşı”, a major institution in tekke music, has been examined with a special focus on Col. Selahaddin Gürer, who was one of the most important zākirbaşıs of the 19th century born in the final years of the Ottoman State. These examinations are aimed at making a scientific contributi on to Turkish religious music by providing a source on the musical performance and choreographic aspect of tekke music for those doing research in this particular field. Although the forms of congregational remembrance are not limited to the qiyāmī and qu'ūdī (sitting) rites --there is also the dawrānī (circles of remembrance) rite--, because of the need to limit our study, we examined in detail the choreography and musical parts of the two particular types mentioned, and the dawrānī rite was touched on only briefly. As the main source of Kıyâm Kelime-i Tevhîdi, we benefited from a number of recordings made in the 1960s on reel-to-reel tape recorders; these recordings formed the basis of our research and they were carefully examined and notated. In this research, the established academic methods of literature reviewing and classification were used. The data used in the thesis were obtained by scanning the dissertations written in the academic field of Turkish Religious Music, interviews done with the experts of the field, academic articles as well as numerous books on the topic. The findings were duly classified and dealt with in a systematic way.
Keywords: Albay; Albay Selahattin Gürer; History; Islam; İslamiyet; Kıyâm Kelime-i Tevhîdi; Music of Tekke; Qıyam Word of Tewhid; Tarih; Tekke Mûsikîsi; Turkish Religious Music; Türk Din Mûsikîsi; Zâkirbaşı